Chapter Die ,Privaturkunde' im persisch-islamischen Kultur- und Rechtsbereich. Herausforderungen einer komparatistischen Diplomatik - Werner, Christoph U. (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2019)
The European Middle Ages are generally considered to be the "age of the charter," but there are also charters of various types handed down from other pre-modern cultures. These documents are now no longer seen as mere "textual recordings," but as objects of symbolic communication. The aim of this volume is to show the possibilities offered by the analysis of charters for answering general questions in cultural and social history.